Inhibition of DNA Methylation With Zebularine Alters Lipopolysaccharide-Induced Sickness Behavior and Neuroinflammation in Mice - Matt, Stephanie M.; Zimmerman, Jalisa D.; Lawson, Marcus A.; Bustamante, Angela C.; Uddin, Monica; Johnson, Rodney W. (Frontiers in Neuroscience, 2018)
Activity of DNA methyltransferases (DNMTs), the enzymes that catalyze DNA methylation, is dynamically regulated in the brain. DNMT inhibitors alter DNA methylation globally in the brain and at individual neural plasticity-associated genes, but how DNMT inhibitors centrally influence lipopolysaccharide (LPS)-induced neuroinflammation is not known. We investigated whether the DMNT inhibitor, zebularine, would alter sickness behavior, DNA methylation of the Il-1β promoter and expression of inflammatory genes in hippocampus and microglia. Adult mice treated with an intracerebroventricular (ICV) injection of zebularine prior to LPS had faster recovery of burrowing behavior compared to mice treated with LPS. Further, genes of inflammatory markers, epigenetic regulators, and the microglial sensory apparatus (i.e. the sensome) were differentially expressed by zebularine alone or in combination with LPS. Bisulfite pyrosequencing revealed that ICV zebularine led to decreased DNA methylation of two CpG sites near the Il-1β proximal promoter alone or in combination with LPS. Zebularine treated mice still exhibited decreased DNA methylation 48 h after treatment when LPS-induced sickness behavior as well as hippocampal and microglial gene expression were similar to control mice. Taken together, these data suggest that decreased DNA methylation, specifically of the Il-1β promoter region, with a DNMT inhibitor in brain disrupts molecular mechanisms of neuroinflammation.